In situ Raman investigation of dissolved constituent and its evolution in pulp during Zn-S selective flotation with two-step pulp regulation. (February 2023) - Li, Haodong; Yang, Congren; Qin, Wenqing; Tian, Zuyuan; Wu, Changfa; Wei, Qian; Jiao, Fen
Highlights: It was confirmed that soluble polysulfides were generated in pulp with lime. The generated polysulfides remained stable in pulp without Eh regulation. Polysulfides in pulp would soon disappear under the action of Eh regulation. Polysulfides made activation ineffective because CuSO4 was precipitated quickly. Two-step Eh regulation was favorable for Zn-S selective flotation. Abstract: Redox potential (Eh) of the pulp dominates Zn-S selective flotation, and regulating Eh can maximize Zn grade and recovery of Zn rougher concentrates. However, reasons accounting for the beneficial results of Eh regulation in flotation have not been previously elucidated. This study investigated the inherent causes of macro flotation results by inductively coupled plasma optical emission spectrometer (ICP-OES), Raman spectra and X-ray diffraction (XRD) analyses. The ICP-OES data showed that the levels of calcium and sulfur in the pulp increased considerably after lime regulation. The Raman spectra confirmed that calcium polysulfide (CaS n, n = 2–8) was generated and maintained long-term stability in the pulp regulated by lime without Eh regulation. However, under Eh regulation, CaSn only kept momentary existence in the pulp. Polysulfide reacted quickly with the added copper sulfate and formed brown precipitates, whose main component identified by XRD was CuS, leading to the ineffectiveness of copper-activation for Zn flotation. These findings provide a new insight into the role of Eh in sulfide mineral flotation and partially explain the main reasons to hinder the high-efficiency selective separation of sphalerite from pyrrhotite-containing sulfide ores.